Trend of deaths due to circulatory system in Erbil City between 2007 to 2011 - Zangana, Aso H.; Bahoo Al – Banna, Haitham I. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Circulatory diseases are one of the leading causes of death in the world which continue to rise despite preventive measures. Objective: To determine gender, age and cause specific trends of mortality due to circulatory diseases between 2007 and 2011 in Erbil city. Methods: A review of registered death records from disease of circulatory system was performed at the statistical unit in Directorate of Health in Erbil city. No special codes for the cause of death were available on death certificate. Statistical analysis was done using SPSS version 19 Results: Diseases of circulatory system was responsible for 25.5% of total deaths during the study period. Highest rates were recorded at 2011 with 74 deaths per100000 population. After 2009, circulatory mortality increased sharply to be the first cause of death till 2011, Stroke, Ischemic heart diseases (IHD), cardiac arrest and heart failure were the main cause of deaths. Most of deaths occur in age group of 65-74 years. Ischemic heart diseases was the main cause of death in male (31.5%) while stroke in female (34.5%) which were statistically significant Conclusion: Circulatory mortality was the second leading cause of death in Erbil city till the year 2009 where it started to increase to be the first cause till 2011. Future preventive public health strategies for circulatory diseases prevention are mandatory.